IMPLEMENTASI KEBIJAKAN MENTERI AGRARIA DAN TATA RUANG TENTANG PERCEPATAN PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KOTA BANDUNG - Asep Hidayat; engkus engkus; Hasna Afra. N (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2018)
This research aims to know the strategy of the Government in the implementation of the programme of PTSL and to find out how big a success rate of Program execution PTSL in Bandung. The results showed that the Government strategy of Bandung Bandung in BPN through program implementation through the preparation of PTSL ripe includes socialization, the determination of the location, planning effort, and the establishment of the Committee ajudikasi acceleration, training and outreach. The success rate of execution of PTSL in Bandung from the target amount of the targeted land certificate 93,000 just 7,234 certificates or reached only 7.78% of the data that researchers get. This is caused by a number of working groups, the situation is not comparable with the volume so that the targets set in the achievement of the targets still not be met.